Persepsi Stakeholder Terhadap Upaya Pencegahan Perdagangan Satwa Liar Di Kota Sorong - Maya Pattiwael; Amatus Turot; Cindy Rismawati Iman (Universitas Muhammadiyah Sorong, 2025)
Abstract Wildlife trade and smuggling require attention from various parties. In West Papua, wildlife smuggling is common and is usually thwarted in Sorong City, the main gateway for various wildlife transactions. This study aims to determine stakeholder perceptions, prevention efforts, inhibiting factors, and contributing factors to wildlife trafficking. The study was conducted from June to August 2023. Sampling was conducted using purposive sampling, while data collection was conducted through interviews with five respondents from the West Papua Natural Resources Conservation Center (BKSDA), the Sorong Class 1 Agricultural Quarantine Station, and the West Papua Regional Police's Water and Air Police Directorate. The data obtained were analyzed using descriptive qualitative methods. The results indicate that efforts to prevent wildlife trafficking in Sorong City have been implemented using preventive, preemptive, and repressive approaches. However, obstacles remain, such as low public awareness, increasingly diverse smuggling methods, and limited staff. Wildlife trafficking is largely driven by economic factors, social motives, and a lack of education and supervision. Community involvement is also an important factor in providing information and making it easier for officers to thwart animal smuggling attempts.